slamic Finance and Sustainable Development in Nigeria: Assessing the Role of Non-Interest Banking in Poverty Reduction and SME Growth - Jamiu Adeniyi Yusuf (CV Media Inti Teknologi, 2025)
Background of study: This paper examines the intersection of Islamic finance and sustainable development within the Nigerian context. As Nigeria grapples with significant developmental challenges, this study explores how financial models rooted in Islamic principles align with the United Nations' Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure).Aims and scope of paper: The study specifically assesses the role of non-interest banking in fostering poverty reduction and the growth of Small and Medium-sized Enterprises (SMEs). This work investigates the mechanisms through which Islamic financial instruments like Murabaha, Mudarabah, Musharakah, and Sukuk are deployed to support pro-poor initiatives and empower entrepreneurs.Methods: Through a systematic review of existing literature, regulatory frameworks, and operational data from Nigerian non-interest banks such as Jaiz Bank, Taj Bank, and Lotus Bank, this study explores the topic.Result: The analysis reveals a strong theoretical and practical congruence between the objectives of Islamic finance, which emphasize ethical investment, risk-sharing, and asset-backed transactions, and the core tenets of sustainable development. The findings indicate that while non-interest banking holds considerable potential to drive inclusive growth by expanding financial access to underserved populations and providing patient capital for SMEs, its impact is constrained by challenges including low public awareness, regulatory complexities, and human capital deficits.Conclusion: The paper concludes by offering policy recommendations aimed at strengthening the non-interest banking sector to more effectively contribute to Nigeria's sustainable development agenda.